PAW31 Clinical and genetic spectrum of the episodic ataxias: the UK perspective. Issue 11 (22nd October 2010) - Rajakulendran, S; Labrum, R W; Graves, T D; Tomlinson, S; Eunson, L H; Davis, M B; Schorge, S; Kullmann, D M; Hanna, M G
Abstract : The episodic ataxias are an exemplar of ion channelopathies, encompassing many of the common features that typify this rapidly expanding group of disorders. Two distinct forms, EA1 and EA2 are caused by mutations in the neuronal potassium (KCNA1) and calcium (CACNA1A) channel genes respectively. They are characterised by paroxysmal attacks of cerebellar dysfunction. In this study, we present the clinical, genetic and molecular expression results of mutations identified in a series of over 100 families from the UK who presented with clinical episodic ataxia over the last 15 years. We report a number of key findings: first, both disorders are associated with a wide phenotypic spectrum. Second, genetic variation in CACNA1A is associated with human epilepsy in addition to EA2. Third, large deletions of CACNA1A in EA2 account for 10% of cases, results which have an important impact on diagnostic testing. Fourth, molecular studies of all expressed mutations demonstrate a loss of channel function as critical in disease pathogenesis. Our findings broaden the range of clinical features and mutations associated with the episodic ataxias and have lead directly to a DNA diagnostic service. Furthermore, our findings indicate that loss of channel function is a key disease mechanism and highlight genetic heterogeneity, suggesting there are additional new channel genes responsible for episodic ataxia.